Aspects of cognitive performance relating to Theory of Mind (ToM) among people diagnosed with Post-Traumatic Stress Disorder (PTSD) - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2019)
Objective: This study investigated Theory of Mind (ToM) abilities as measured by a hinting task and the Reading the Mind in the Eyes Test (RMET) in individuals diagnosed with post-traumatic strees disorder (PTSD) in relation to different types of childhood trauma and compared to a healthy control group. Method: RMET, a Clinician Administered PTSD Scale (CAPS), a Beck Depression Inventory (BDI), a Childhood Trauma Questionnaire (CTQ), a hinting task, and a socio-demographic questionnaire were administered to PTSD (n=30) patients and healthy controls (n=30). Results: There was a significant difference in ToM performance between healthy participants and the PTSD group (p<0.001). A significant correlation was found between trauma types and ToM performance (p<0.01). The diagnosis of PTSD and the severity of PTSD symptoms showed significant correlations with ToM performance (p<0.01). In comparison with the healthy control group, the PTSD group demonstrated lower performance on both ToM tasks. Regardless of the PTSD diagnosis, those people who had a history of childhood trauma had slowed reaction times in response to photographs representing emotionally salient mental states and demonstrated difficulties in the identification of irony/hints in the context of the administered assessment task. Conclusion: The findings of the present study suggest that a diagnosis of PTSD and a history of different types of trauma have an effect on ToM performance PTSD seems to lead to deterioration in ToM capacities. This may mean that the experience of childhood adversity may lead to long-lasting damage to social cognition. The current study is helpful in that it contributes to a better understanding of the pathogenesis of PTSD; moreover, it will be beneficial in the development of new treatment options. Our research findings suggest that we must concentrate not only on traumatic events during the treatment process of PTSD follow-up and treatment; we must also target deficiencies in cognitive and emotional capabilities.
Keywords: PTSD; Theory of Mind; ToM; trauma; trauma types; CHILD MALTREATMENT; EYES TEST; TRAUMA; RECOGNITION; RELIABILITY; VALIDITY; EMPATHY; ADULTS; WOMEN; TASK